Crumbs protein homolog 3 (CRB3) expression is associated with oestrogen and progesterone receptor positivity in breast cancer. (10th June 2019) - Li, Pingping; Zhou, Can; Yan, Yu; Li, Juan; Liu, Jie; Zhang, Yan; Liu, Peijun
Abstract: The crumbs protein homolog 3 (CRB3) regulates the tight junction to help maintain epithelial polarity. Altered CRB3 expression was associated with carcinogenesis of epithelial cells. This study detected CRB3 expression in 192 cases of breast cancer tissues and in the Molecular Taxonomy of Breast Cancer International Consortium (Metabric) and The Cancer Genome Atlas (TCGA) datasets for association with triple negative breast cancer (TNBC) phenotypes. The in vitro experiments confirm the ex vivo data. The data showed that levels of both CRB3 mRNA and protein were associated with TNBC phenotypes, ie, 41.1% (39/95) of ER+ breast cancer was CRB3‐positive, whereas 26.9% (25/93) ER– tumour was CRB3‐positive ( P  =   0.046). Moreover, 47.6% (30/63) of PR+ breast cancer was CRB3‐positive vs 28.4% (33/116) PR‐ tumours positive for CRB3 ( P  =   0.013). In addition, 40.1% (27/66) of ER+/PR+ tumour was CRB3‐positive, but only 22.4% (19/85) of TNBC showed CRB3 expression ( P  =   0.048). Indeed, levels of CRB3 mRNA were higher in non‐TNBC than TNBC in both Metabric ( P  =   3.682e‐10) and TCGA datasets ( P  =   2.501e‐07). The in vitro data showed that CRB3 expression was higher in luminal (MCF7 and T47D) than in HER2 (MDA‐MB‐453 and SK‐BR‐3) and basal (MDA‐MB‐231 and BT‐549) breast cancer cell lines. More interestingly, ERα regulated expression of CRB3 protein in MCF7 and BT‐549 cells and ERα expression was associated with CRB3 expression in breast cancer tissues specimens. This study demonstrated that ERα could be a novel regulator for CRB3 expression in breast cancer.